Gingival Health Status among Patients Wearing Fixed Orthodontic Appliance in Erbil City - Abdullah, Dr. Dildar; Omer, Dr. Zana Qadir; Taha, Dr. Maryam H. (South Eastern European Journal of Public Health, 2024)
Objectives and background: People have increasing demand for orthodontic treatment and it became a common treatment plan nowadays that may affect the gingival health. However, the correlation between orthodontics and periodontal health is not clear, which troubles the clinical orthodontist during planning of the treatment. So many studies showed previously a relationship between orthodontic appliance and the dental diseases that it may cause. This study aimed to evaluate the relationship between gingival health status and the duration of wearing fixed orthodontic appliance. Method: The study included 40 patients wearing fixed orthodontic appliance. Patients’ folders were analyzed according to the duration of wearing the appliance and route of breathing then comparing these two factors and their effects on plaque index, gingival index and gingival sulcus depth. Results: As the duration of wearing the appliance increased, there was an increase in the plaque accumulation and gingival bleeding on probing, except for the forth group of duration (more than 12 months with the appliance). As for breathing factor, the findings were as the following (In order from less plaque accumulation to the most, respectfully): nasal, both (nasal and mouth) and finally mouth, while with the gingival index, the data showed the opposite. Conclusion: Prolonged orthodontic treatment was associated with an increased plaque retention and increased bleeding on probing; however, the magnitude of the difference in gingival sulcus depth in both duration of wearing the appliance and different breathing routes was of no clinical significance. Breathing orally had negative effect on the oral hygiene.